Innovative Strategies in Educational Administration Management at MTs An-Nashir - Salma Gania; Astuti Darmiyanti (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
The educational administration management strategy at MTs An-Nashir involves the integration of financial applications, student data collection, and teacher administration. The use of applications such as